MAIN EDUCATIONAL THEORIES AFFECTING THE DESIGN AND IMPLEMENTATION OF THE LEARNING ENVIRONMENT BASED ON INFORMATION TECHNOLOGIES - Inagamova Nargis Abdullayevna (Web of Journals Publishing, 2025)
This article explores the application of major educational theories in the design and implementation of learning environments based on information technologies (IT). It examines how theories such as constructivism, behaviorism, connectivism, and collaborative learning influence modern educational practices and the creation of interactive digital learning environments. The article highlights the role of IT in enhancing engagement, providing personalized learning experiences, and promoting collaborative work among students. Through a combination of theoretical insights and practical examples, it demonstrates how these theories can guide the effective use of digital tools like e-learning platforms, mobile applications, and virtual simulations in supporting student learning. Despite the promising potential of IT, challenges such as unequal access to technology and the need for teacher training are also discussed. The article concludes that understanding and integrating educational theories with IT tools is essential to creating dynamic, effective, and inclusive learning environments.
Keywords: Information Technology (IT), Educational Theories, Constructivism Behaviorism, Connectivism, Collaborative Learning, E-Learning, Digital Learning Environments, Personalized Learning, Interactive Learning.